Overcoming impunity: pathways to accountability in Latin America - Lessa, Francesca (International journal of transitional justice, 2014)
How and why do democratic governments overcome amnesty laws and cultures of impunity to allow for trials for past human rights violations? To confront this question, we first identify widespread agreement on four key factors associated with the degree of accountability in a new democracy: civil society demand, domestic judicial leadership, the absence of veto players and international pressure. We then outline the interactions among those factors that lead to four distinct scenarios of overcoming amnesty, from the failure to do so (obstinate amnesties) to successful democratic displacement of amnesties and the proliferation of trials. Because Latin America has had great variation in these accountability pathways, we use it as a test region to examine the dynamic interaction of the four key factors in overcoming impunity. We conclude by considering this new dynamic interaction framework outside Latin America.